Design Of A Vba-Based Financial Recording And Transaction Tracking Application In Excel At Kartika Laundry, South Jakarta City - Shintya Permatahati; Inanda Shinta Anugrahani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to design and implement a financial recording application based on Microsoft Excel, utilizing Visual Basic for Applications (VBA), for the micro, small, and medium enterprise (MSME) Laundry Kartika. The main problem identified is the lack of internal control in financial recording practices, which are still carried out manually without adequate recording procedures, resulting in transaction data that are not systematically documented and are at risk of loss or distortion of financial information. In addition, the absence of an effective accounts receivable and payable tracking mechanism causes credit transactions to often go unrecorded, which may lead to uncollectible receivables and reduce the reliability of financial reports. The developed application, AKLUN (Aplikasi Akuntansi Laundry), provides key features such as automated transaction input, preparation of general journals and ledgers, presentation of income statements and balance sheets, a fixed asset depreciation tracker, and a user authentication-based security system. The application development was carried out using the waterfall model, which includes stages of needs analysis, system design, implementation, testing, and maintenance. The implementation results indicate that AKLUN can improve the regularity and consistency of transaction recording, enhance financial documentation from previously unstructured to more systematic and well-documented, and provide an accountable and reliable accounts receivable and payable tracking mechanism. Thus, AKLUN serves as a relevant, effective, and adaptive digital solution to support efficient and responsive financial management for MSMEs in the context of digital transformation.